2011
DOI: 10.1002/bsl.1004
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Situational Correlates of Self‐reported Reasons for Intimate Partner Violence among Women versus Men Referred for Batterers' Intervention

Abstract: This study examines personality and situational correlates of self-reported reasons for intimate partner violence (IPV) among women and men court-ordered to batterers' intervention as IPV offenders. Women endorsed self-defense and men retaliation as their primary reasons for IPV. Both also endorsed emotion dysregulation as a reason for much of their violence. Women's partner violence was largely, but not exclusively, situationally motivated. Women's reasons for violence also related significantly to self-repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
39
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 34 publications
2
39
0
3
Order By: Relevance
“…However, findings across studies are quite mixed with some suggesting a stronger association for women and others suggesting a stronger association for men. In a nationally representative sample (Ross, 2011), for both men and women, emotional dysregulation was strongly related to both borderline traits and defensive violence, whereas retaliatory violence was associated with BPD in men, but not in women (rather, this type of violence in women was associated with situational contexts). Walsh and colleagues (2010) found that female perpetrators with B/D traits were most likely to be characterized by victimization, compared to their male B/D counterparts who were more likely to be characterized by additional antisocial traits.…”
Section: Resultsmentioning
confidence: 96%
“…However, findings across studies are quite mixed with some suggesting a stronger association for women and others suggesting a stronger association for men. In a nationally representative sample (Ross, 2011), for both men and women, emotional dysregulation was strongly related to both borderline traits and defensive violence, whereas retaliatory violence was associated with BPD in men, but not in women (rather, this type of violence in women was associated with situational contexts). Walsh and colleagues (2010) found that female perpetrators with B/D traits were most likely to be characterized by victimization, compared to their male B/D counterparts who were more likely to be characterized by additional antisocial traits.…”
Section: Resultsmentioning
confidence: 96%
“…This association is less consistent in the literature partly because IPV is a complex phenomenon which may not be fully explained by a single factor or simple model [7], [23], [24]. For example, sensation seeking was associated with IPV perpetration among couples in one study [25], but not in another study conducted among male undergraduates [26].…”
Section: Introductionmentioning
confidence: 82%
“…For example, Harned (2001) compared men and women’s motives for dating violence and found that women were more likely to perpetrate physical aggression because of anger/jealousy than men. Similarly, in a sample of men and women court-ordered to batterer intervention programs (BIPs), Ross (2011) found that women were more likely to report being violent in response to infidelity than men. Results further indicated that men were more likely to report retaliation and women self-defense as primary motivators for partner aggression.…”
mentioning
confidence: 99%